SALINGKA KATO - Laila Okta Triani; Asep Saepul Haris; Nursyirwan; Ediwar (Journal of Innovation Research and Knowledge, 2021)
Salingka Kato is the title of a compositional creation of Indonesian music originating from the phenomenon of the customary system in Jorong Pabalutan, Kanagarian Rambatan. The choice of title was related to the context and consideration of the form of working for the creation as a whole. The customary system found in the Jorong Pabalutan Kanagarian Rambatan community became the source of the work creation. The contexts obtained from the research were regeneration, socialization and synchronization. The creation effort which was done to interpret the context was to make an analogy into the work of music by considering the musical capital and the form of the work. The first part is about interpreting the deal that developed in the demands of regeneration with tittle of work Babalah Sibak Baju. The second part is about interpretation effort on dialectics that happen because of dissent in deliberation and congregation. On the third part, the interpretation about the differences can be accepted by the public with a Sasuai tittle. The work approach used in the embodiment of Salingka Kato's work was Re-Interpretation and the form of the work creation presented was not related to the musical culture used.